Pulsed plasma flow diagnostics - Tazhen, A.B.; Dosbolayev, M.K.; Ramazanov, T.S. (Recent Contributions to Physics, 2022)
This paper presents the results of optical and probe diagnostics of hydrogen plasma flow in a coaxial plasma accelerator. The triple probe and the Optosky ATP2000P linear spectrometer with a spectral range of 200-1100 nm were used for measuring the electron current and obtaining the hydrogen plasma emission spectrum. The individual spectral lines were observed using an M833 monochromator spectrometer with a spectral resolution of 0.024 nm. From the measured electron currents and emission spectrums, the electron densities in the flux of a hydrogen pulsed plasma were calculated. We used the Stark method of Hβ hydrogen line broadening for calculations of electron densities. The obtained experimental results from the probe and spectroscopic measurements of electron density correspond well. In this work, we also obtained the dependence of the electron density on the voltages applied to the capacitor bank. The electron density increases with increasing voltage, because of the increased energy applied to the discharge. The average electron densities in the plasma flux showed 1.13 ∙ 1021 m-3, 4.14 ∙ 1021 m-3, and 5.57 ∙ 1021 m-3 at three values of voltages of 3 kV, 4 kV, and 5 kV, respectively.